Interplay of Regulatory T Cell and Th17 Cells during Infectious Diseases in Humans and Animals - Sehrawat, Sharvan; Rouse, Barry T. (Frontiers in Immunology, 2017)
It is now clear that the outcome of an inflammatory process caused by infections depends on the balance of responses by several components of the immune system. Of particular relevance is the interplay between regulatory T cells (Treg) and CD4+ T cells that produce IL-17 (Th17 cells) during immunoinflammatory events. In addition to discussing studies done in mice to highlight some unresolved issues in the biology of these cells, we emphasize the need to include outbred animals and humans in analyses. Achieving a balance between Treg and Th17 cells responses represents a powerful approach to control events during immunity and immunopathology.